Assessment of TOC and TPM in Indian SME Auto Manufacturing Industries. Issue 2 (December 2021) - Tarte, Nagesh; Doke, Sunil
The purpose of this article is to investigate the impact of theory of constraints (TOC) and total productive maintenance (TPM) practices on operational performance, and their interlinkage between each other. Constructs that are critical to auto manufacturer's operational performance have been identified with the help of literature and experts from industry. The impact of TOC and TPM on operational performance has been evaluated. Similarly, impact of competitiveness on operational performance has been evaluated. Further, alternate models are tested and evaluated through structural equation model. It was observed during testing of alternate models that TOC and TPM have a direct impact on operational performance. However, TOC and TPM practices also directly impact overall operational performance, which in turn, influences competitiveness. In comparison of alternate models, the model in which TOC and TPM affect overall equipment efficiency (OEE), human total participation and commitment (HTPC), throughput (T), inventory (I), and operating expense (OE) practices and these further affect the operational performance, is found most appropriate. This study provides some useful implications from industry point of view. TOC and TPM practices are crucial to auto manufacturing industries. TOC and TPM are the core of attaining sustenance in crucial factors, which will have greater impact to achieve operational performance. Overall equipment efficiency, Human total participation, T, I, and operating expense practices are driven by TOC and TPM practices. This crucial factor linkage helps to achieve the desired operation performance. There are very limited studies that have considered both the continuous improvement practices together to achieve better operational performance. In auto manufacturing industry, both TOC and TPM are crucial continuous improvement practices for any organization to drive its growth.